Dissolved munition compounds in the water column measured during ALKOR cruise AL548, southwestern Baltic Sea - Beck, Aaron; Arinaitwe, Kenneth; Greinert, Jens; Achterberg, Eric Pieter (PANGAEA, 2025)
Cruise AL548 (R/V Alkor) sampled the water column in German territorial waters of the southwest Baltic Sea during 04-16 November 2020. This dataset contains concentrations of dissolved munition compounds from 73 Niskin bottle rosette casts between sea surface and seafloor. Vertical sampling resolution varied among stations, with a maximum of 5 sampling depths. Dissolved explosives in the samples were measured following Gledhill et al. (2019). Briefly, discrete samples (1 L) were preconcentrated onboard using solid-phase extraction. Target compounds were eluted with acetonitrile, further concentrated by evaporation, and measured by ultra-high performance liquid chromatography and high resolution heated electrospray ionization mass spectrometry.
Keywords: Baltic Sea; DNB; Dumped munitions; explosive chemicals; Marine environments; Marine Pollution; Munition compounds; RDX; TNT; World War II